SISTEM MACHINE LEARNING YOU ONLY LOOK ONCE UNTUK IDENTIFIKASI PELAKU PEMBUANG SAMPAH SECARA REAL-TIME - Wahyuda, Muhammad Jefi (Teknik Elektro Polsri, 2025)
The This research develops a real-time litterer recognition system using image processing techniques based on the You Only Look Once (YOLO) model. The problem of littering is a serious environmental issue that requires immediate attention to maintain cleanliness and public health. The proposed system aims to automatically detect and identify litterers through video analysis recorded by surveillance cameras. Test results show that the developed system can detect litterers with 100% accuracy in bright conditions and 80% accuracy in dark conditions, effectively in real-time. The implementation of this system is expected to assist the government and related agencies in reducing cases of littering and raising public awareness about the importance of maintaining environmental cleanliness.